Gas chromatography-mass spectrometry based profiling reveals six monoglycerides as markers of used cooking oil. (February 2019) - Cao, Guodong; Ding, Cheng; Ruan, Dongliang; Chen, Zhaobin; Wu, Huiqin; Hong, Yanjun; Cai, Zongwei
Abstract: Under deep frying conditions, edible oil will release a variety of deterioration chemicals that have been implicated in many diseases. Unscrupulous traders may refine used cooking oil and adulterate it as qualified edible oil, thus posing threats to public health. This research aimed to discover the chemical markers of used cooking oil by using gas chromatography-mass spectrometry (GC-MS) based profiling. Our results suggested that six monoglycerides could be used as endogenous markers to discriminate used cooking oil from fresh edible oil. Accumulation behaviors of those markers in continuous heating process were observed. A quantitative GC-MS method was further developed for the six monoglycerides with good accuracy, precision and reproducibility. This method enabled the authentication of commercial olive oil adulterated with 1% deep fried oil. Abnormally high levels of the monoglycerides markers had also been determined in 116 gutter oil samples. Therefore, quantitation of six monoglycerides markers by GC-MS could be a promising approach for elucidating the degradation state of edible oil, authenticating commercial oil products adulterated with used cooking oil, as well as screening of gutter oil. Highlights: Six monoglycerides are identified as endogenous markers of used cooking oil. The levels of monoglycerides in in-house heated oils were continuously increased. Abnormally high levels of monoglycerides were detected in deep fried oil and gutter oil. This method enabled authentication of olive oil adulterated with trace deep fried oil.